The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1186/s12876-018-0761-7
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranylacetone attenuates fibrogenic activity and induces apoptosis in cultured human hepatic stellate cells and reduces liver fibrosis in carbon tetrachloride-treated mice

Abstract: BackgroundGeranylgeranylacetone (GGA), an anti-ulcer drug widely used in Japan, has attracted interest because of its various therapeutic effects. Therefore, we investigated the effects of GGA on human hepatic stellate cells (HSCs) in vitro and in a mouse model of liver fibrosis.MethodsLX2, an immortalized human HSC line, was cultured and treated with GGA at concentrations up to 0.5 mM. After GGA treatment, changes in cellular morphology, apoptosis, and fibrosis-related gene expression were assessed. Male C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In many cases, the cytotoxicity of copper complexes originates from the generation of ROS driven by the metal. Meanwhile, ROS plays a significant role in apoptosis activation by many chemotherapeutical drugs and radiation treatments [36, 37]. In the case of abnormal metabolism and signaling, tumor cells are well adapted to the unbalanced redox state through improved antioxidant capacity and oncogenic signaling pathways [22].…”
Section: Resultsmentioning
confidence: 99%
“…In many cases, the cytotoxicity of copper complexes originates from the generation of ROS driven by the metal. Meanwhile, ROS plays a significant role in apoptosis activation by many chemotherapeutical drugs and radiation treatments [36, 37]. In the case of abnormal metabolism and signaling, tumor cells are well adapted to the unbalanced redox state through improved antioxidant capacity and oncogenic signaling pathways [22].…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that DC-IL10 could inhibit the inflammatory response and the activation of HSCs by regulating the imbalance of Treg/Th17 in liver fibrosis. Inhibiting the activation of HSCs has become a critical treatment strategy for liver fibrosis [26]. Previous investigations have confirmed that the TGF- β /smad signaling pathway plays an important role in the activation of HSCs and is considered as a crucial mechanism during the progress of liver fibrosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that GGA induces endoplasmic reticulum (ER) stress in hepatoma cells and hepatic stellate cells 22 . Additionally, it has been reported that ER stress reduces hepatic transcriptional factors 23 .…”
Section: Resultsmentioning
confidence: 99%
“…30 Senoo et al also reported that GGA induced ER stress in hepatoma and stellate cells. 22 Additionally, Vachirayonsti et al reported that HNF4α was downregulated during ER stress. 23 Similarly, in our study, GGA treatment induced ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation